2019
DOI: 10.1590/0037-8682-0044-2019
|View full text |Cite
|
Sign up to set email alerts
|

Secondary syphilis with pulmonary involvement mimicking lymphoma: a case report

Abstract: We present a case of atypical presentation of secondary syphilis with extensive lymph node involvement and pulmonary lesions, initially suspected as lymphoma. The patient presented with weight loss, dry cough, chest pain, palpable lymph nodes in several peripheral chains, and multiple pulmonary nodules and masses on chest imaging. The key features for secondary syphilis diagnosis were a lymph node biopsy suggestive of reactive lymphadenopathy, positive serologic tests for syphilis, and complete recovery after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In fact, in many cases, a lung biopsy was either not performed or not included, and treatment was based on serological confirmation and associated clinical features. 24,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Although not specifically stated, some descriptions suggest the morphology of an IPT 12,19 while others showed varied morphology (Table 1). Granulomas, seen in 5 cases, and lymphoplasmacytic infiltrates were the most common findings.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in many cases, a lung biopsy was either not performed or not included, and treatment was based on serological confirmation and associated clinical features. 24,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Although not specifically stated, some descriptions suggest the morphology of an IPT 12,19 while others showed varied morphology (Table 1). Granulomas, seen in 5 cases, and lymphoplasmacytic infiltrates were the most common findings.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute pneumonia revealed the diagnosis in the case reported by Campos et al [ 8 ]. Florencio et al [ 9 ] reported syphilitic pulmonary involvement mimicking lymphoma with polyadenopathy and pulmonary nodules. Kassem Youssef et al [ 10 ] reported a case of syphilitic pulmonary involvement revealed by dyspnea, with thoracic imaging showing interstitial lung pattern, moderate pleural effusion, and hilar lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient met the diagnostic criteria of pulmonary syphilis, which include typical findings of syphilis in other organs, positive serological findings, imaging abnormalities that cannot be explained by other conditions, and response to syphilis treatment 2 . However, pulmonary syphilis can occur without the typical cutaneous lesions 3 . The imaging findings of pulmonary syphilis include multiple nodules 2 and/or masses 3 simulating primary lung neoplasia or metastases, and abscesses 1 with or without mediastinal lymph node enlargement.…”
mentioning
confidence: 99%
“…However, pulmonary syphilis can occur without the typical cutaneous lesions 3 . The imaging findings of pulmonary syphilis include multiple nodules 2 and/or masses 3 simulating primary lung neoplasia or metastases, and abscesses 1 with or without mediastinal lymph node enlargement. 18 F fluorodeoxyglucose (18F-FDG) positron emission tomography-CT may show intense 18F-FDG uptake by the lesions 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation